3D Printed Poly(ε-Caprolactone)/Meniscus Extracellular Matrix Composite Scaffold Functionalized With Kartogenin-Releasing PLGA Microspheres for Meniscus Tissue Engineering - Li, Hao; Liao, Zhiyao; Yang, Zhen; Gao, Cangjian; Fu, Liwei; Li, Pinxue; Zhao, Tianyuan; Cao, Fuyang; Chen, Wei; Yuan, Zhiguo; Sui, Xiang; Liu, Shuyun; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Meniscus tissue engineering (MTE) aims to fabricate ideal scaffolds to stimulate the microenvironment for recreating the damaged meniscal tissue. Indeed, favorable mechanical properties, suitable biocompatibility and inherit chondrogenic capability are crucial in MTE. In this study, we present here a composite scaffold by 3D printing a poly(ε-caprolactone) (PCL) scaffold as a backbone, followed by injection with the meniscus extracellular matrix (MECM) and modified it with kartogenin (KGN)-loaded PLGA microsphere (μS), which serves as a drug delivery system. Therefore, we propose a plan to improve meniscus regeneration via KGN released from the 3D porous PCL/MECM scaffold. The final results showed that the hydrophilicity and bioactivity of the resulting PCL/MECM scaffold were remarkably enhanced. In vitro synovium-derived mesenchymal stem cells (SMSCs) experiments suggested that the introducing MECM components helped cells adhesion, proliferation and maintain promising ability to induce cells migration. Moreover, KGN-incorporating PLGA microspheres which were loaded on scaffolds showed a prolonged release profile and improved the chondrogenic differentiation of SMSCs during the 14-day culture. Particularly, the PCL/MECM-KGN μS seeded by SMSCs showed the highest secretion of total collagen and aggrecan. More importantly, the synergistic effect of the MECM and sustained-released KGN, can endow the PCL/MECM-KGN μS scaffolds with not only excellent cell affinity and cell vitality preservation, but also chondrogenic activity. Thus, the PCL/MECM-KGN μS scaffolds are expected to have good application prospects in the field of MTE.